Primary solitary pituitary stalk abscess: case report and review - Ma, Yuehui; Bu, Linghao; Jin, Jing (Frontiers in Endocrinology, 2025)
IntroductionPituitary stalk (PS) abscess has not been previously reported. In this study, we report a case of PS abscess presenting with central diabetes insipidus (CDI), hypopituitarism, hyperprolactinemia, and blurred vision. We highlight radiological clues and pathological biopsy findings to clarify the diagnosis and review the literature.Case presentationA 67-year-old female presented with a > 3-month history of bitter and dry mouth, polyuria, blurred vision, fatigue, and poor appetite without inducement. Laboratory investigations revealed CDI, pituitary-thyroid, and pituitary-gonadal axis hypofunction, decreased insulin-like growth factor-1, and slightly elevated prolactin levels. Magnetic resonance imaging (MRI) revealed an isolated cystic, thickened PS with ring enhancement. The patient underwent transsphenoidal surgery. Direct observation during surgery revealed a PS abscess and pale-yellow pus. Histopathological evaluation showed PS tissue with inflammatory cell invasion and lymphocyte proliferation. The patient was treated with linezolid and ceftriaxone for 4 weeks post-surgery and levothyroxine, hydrocortisone, and desmopressin replacement therapy. MRI showed no signs of recurrence of the PS abscess 3 years post-surgery.ConclusionThis case reports a newly identified solitary PS lesions characterized by cystic PS thickening and ring enhancement on MRI, presenting with CDI, hyperprolactinemia, hypopituitarism, and blurred vision. The patient recovered uneventfully, and the postoperative MRI was normal without any recurrent lesions.